Air Layering Trials in Azadirachta indica A. Juss - Mishra, V. K.; Chaukiyal, S. P.; Pal, Mohinder (Indian Forester, 2002)
Air layering trials were conducted in Neem (Azadirachta indica A. Juss) during the months of February, May and August in areas of Uttaranchal and Punjab. One year old lateral branches were girdled, and IBA 500-1000 ppm was applied at the exposed surfaces and wrapped with moistened sphagnum moss. Callus was formed at the girdled portions of all the air layers, with/or without IBA treatments. Adventitious rooting was obtained in the air layers of February and May while the layers made during August failed to form roots. Even the slight delay in air layering trials during monsoon period may suppress air layering response in Neem. The results of our study suggests that early summer season (May) seems to be best period for air layering in Neem and rooting was obtained within two months following girdling.